THEORY AND METHODOLOGY OF PHYSICAL EDUCATION, SPORTS TRAINING, HEALTH-IMPROVING AND ADAPTIVE PHYSICAL CULTURE - Beysenova Aizada Dayrabaevna (Modern American Journals, 2025)
The socioeconomic transformations of the last decade, which have shaped shifts in educational and scientific paradigms, have naturally led to the need to combine education with individual health, the foundations of which, as is generally recognized, are laid in school and developed, reinforced, and refined during college, primarily through physical education and sports.